(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
André Neher writes in his book Ils ont refait leur âme: «Genesis and Exodus meet at the crossroads of Who? and Where?». «The problem of Jewish identity», in fact, cannot be addressed starting «from the question: “Who are you?”. The Jew is related to the first question posed by God to Adam in Genesis: “Where are you?”. In the Hebrew problematic, it is of the same identity as God». Instead, Pharaoh, urged by Moses for the sake of the Jews’ freedom, asks: “Who is God?”. As in: I do not know Him. Neher explains: «You cannot ask: “Who is God?”. That would be denying it. All you can ask is: “Where is God?”».